Nanojet impingement cooling of an isothermal surface in a partially porous medium under the impact of an inclined magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Springer, 2020)
In this study, jet impingement heat transfer characteristics for a layered nanofluid and porous domains under the effects of inclined uniform magnetic field are examined by using Galerkin weighted residual finite element method. Effects of various pertinent parameters such as Reynolds number (between 100 and 500), Hartmann number (between 0 and 6), magnetic inclination angle (between 0 and 90), Darcy number (between10-4\ and height of porous layer (between 0.25 Hand 4 H) on the fluid flow and heat transfer are analyzed. It was observed that local and average heat transfer rate enhance when the value of Reynolds number, magnetic field inclination angle and permeability of the porous layer increase, while the impact is reversed for magnetic field strength. Magnetic field inclination angle has more influence on the convective heat transfer features as compared to strength, and for a horizontally aligned magnetic field heat transfer process is inefficient. When cases in the absence and presence of magnetic field (at Hartmann number of 6) are compared,28% of reduction in the average heat transfer is obtained. An optimum value of porous layer height is observed where the highest heat transfer rates are achieved.
Keywords: MHD nanofluid; Jet impingement; Finite element method; Porous medium